High-selectivity magnesium-lithium separation nanofiltration membrane based on polyolefin-based membrane as well as preparation method and application of high-selectivity magnesium-lithium separation nanofiltration membrane
Through the reverse interface polymerization technology of polyolefin-based film, a nanofiltration membrane with high selectivity was prepared, which solved the problem of poor separation performance of magnesium lithium in salt lake brine, and achieved efficient magnesium lithium separation and reduced production costs.
Patent Information
- Application Number
- CN202411209739.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-08-30
AI Technical Summary
The prior art has poor magnesium lithium ion separation performance in the process of magnesium lithium separation in salt lake brine, resulting in high production costs. In addition, traditional nanofiltration membranes lack the performance of magnesium lithium ion separation, making it difficult to effectively separate high magnesium lithium-specific solutions.
Using polyolefin-based film as the supporting base film, polyvinylamide and isophthalyl chloride or terephthalyl chloride are polymerized in reverse interface to prepare a highly selective magnesium lithium separation nanofiltration membrane to form a high positive electrical properties and a large pore size polyamide layer to improve the separation performance of magnesium lithium ion.
It realizes high-efficiency magnesium lithium separation in high magnesium lithium ion concentration ratio solution, reduces production costs, and is suitable for water treatment and chemical separation fields, with good long-term stability and simplicity of operation.
Smart Images

Figure CN119281115A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a highly selective magnesium-lithium separation nanofiltration membrane, in particular to a highly selective magnesium-lithium separation nanofiltration membrane based on a polyolefin-based membrane and a preparation method and application thereof, belonging to the field of nanofiltration membranes. Background Art
[0002] Since natural lithium-containing brines contain high concentrations of magnesium ions, there are two key indicators for separating and extracting lithium from salt lake brines: lithium content and magnesium-lithium ratio. The current precipitation method consumes a large amount of soda ash to precipitate magnesium before extracting lithium, resulting in high production costs and low economic feasibility. Therefore, it is necessary to separate magnesium ions and lithium ions in advance. Since lithium ions and magnesium ions have very similar chemical properties, the separation and extraction of lithium from brine has become a technical problem currently faced by the chemical industry.
[0003] In early work, researchers applied commercial nanofiltration (NF) membranes to magnesium-lithium separation, and preliminarily verified the feasibility of applying nanofiltration membrane separation technology to lithium extraction from salt lakes. According to the Donnan effect, negatively charged nanofiltration membranes have good retention performance for anions, but insufficient retention capacity for positively charged ions. By analyzing the separation mechanism of nanofiltration membranes, namely the pore size screening effect and the Donnan exclusion effect, it was found that due to the similar size of magnesium and lithium ions (the hydration radius of magnesium ions is 0.43nm, and the hydration radius of lithium ions is 0.38nm), the pore size screening effect plays a limited role in the magnesium-lithium separation process, and the charge of magnesium ions is twice that of lithium ions. Based on this analysis, the electrostatic force between the surface charge of the nanofiltration membrane and the magnesium and lithium ions is the key to improving the magnesium-lithium separation ability of the membrane, and the nanofiltration membrane with a positive surface charge may have a stronger magnesium-lithium separation performance.
[0004] Previous researchers used traditional diamine monomers such as piperazine (PIP) and trimesoyl chloride (TMC) to perform interfacial polymerization on a polyethylene (PE) porous bottom mold, and the resulting multilayer composite polyamide (TFC-PE / PA) nanofiltration membrane was negatively charged, and its magnesium-lithium ion separation performance was poor. Using TMC and polyamine-based polyethyleneimine PEI monomers for reverse interfacial polymerization, the resulting nanofiltration membrane has a high surface positive charge, but its magnesium ion and lithium ion separation performance decreases with the increase of the magnesium-lithium ion concentration ratio in the solution. Therefore, how to obtain a nanofiltration membrane that maintains high magnesium-lithium separation selectivity in a solution with a high magnesium-lithium ion concentration ratio is one of the difficulties in the current magnesium-lithium separation technology. Summary of the invention
[0005] In order to solve the shortcomings of the above-mentioned technology, the present invention provides a highly selective magnesium-lithium separation nanofiltration membrane based on a polyolefin-based membrane, and a preparation method and application thereof. The present invention uses a polyolefin porous membrane as a supporting base membrane, which can greatly reduce the thickness and preparation cost of the membrane, and utilizes polyvinyl amide (PEI) and isophthaloyl chloride or terephthaloyl chloride to perform reverse interfacial polymerization on a polyolefin porous base membrane to prepare a composite nanofiltration membrane with high magnesium ion and lithium ion separation performance, and in a mixed solution containing a high magnesium-lithium ion ratio, has a high magnesium ion interception and high magnesium-lithium separation efficiency.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a highly selective magnesium-lithium separation nanofiltration membrane based on a polyolefin-based membrane, the preparation method being:
[0007] First, a supporting base membrane is soaked in an organic phase solution containing an acyl chloride monomer to obtain a supporting base membrane impregnated with an organic phase monomer, and then the supporting base membrane is soaked in an aqueous phase solution containing an amine monomer for interfacial polymerization. Subsequently, the obtained nanofiltration membrane is activated to obtain a magnesium-lithium separation nanofiltration membrane.
[0008] Preferably, the method specifically comprises the following steps:
[0009] Step S1: dissolving isophthaloyl chloride or terephthaloyl chloride in an organic solvent to obtain an organic phase solution;
[0010] Step S2: dissolving polyethyleneimine monomer in water to obtain an aqueous solution;
[0011] Step S3: soaking the supporting base membrane with the organic phase solution prepared in step S1 to obtain a supporting base membrane infiltrated with organic phase monomers;
[0012] Step S4: immersing the supporting base membrane soaked with the organic phase monomer obtained in step S3 in the aqueous phase solution prepared in step S2 to perform an interfacial polymerization reaction to obtain a polyamide thin film composite nanofiltration membrane;
[0013] Step S5: heat-treating and alcohol-activating the polyamide thin film composite nanofiltration membrane obtained in step S3 to obtain a nanofiltration membrane with magnesium-lithium separation performance.
[0014] Preferably, in the organic phase solution prepared in step S1, the concentration of isophthaloyl chloride or terephthaloyl chloride is 0.05-0.2 w / v%, and the organic solvent is n-hexane.
[0015] Preferably, in the aqueous solution prepared in step 2, the molecular weight of the polyethyleneimine monomer is 700-70000 Daltons, and the concentration of the polyethyleneimine monomer is 0.1-2.0 wt%.
[0016] Preferably, in step S3, the supporting base membrane is a polyolefin porous membrane, and the immersion time is 1-10 min.
[0017] Preferably, in step S4, the reaction time of the interfacial polymerization reaction is 1-10 min.
[0018] Preferably, in step S5, the heat treatment temperature is 30-95° C., the time is 15-60 min, the activation alcohol is isopropanol, and the activation time is 15-60 min.
[0019] The highly selective magnesium-lithium separation nanofiltration membrane prepared by the above preparation method.
[0020] Application of highly selective magnesium-lithium separation nanofiltration membrane in cation separation.
[0021] In the process of preparing nanofiltration membranes, because PEI molecules contain more amino groups, during the reaction, the PA layer formed contains residual amino groups, which make the membrane show a higher positive charge after protonation. Positively charged nanofiltration membranes are generally 2+ , Ca 2+ and Cu 2+ The nanofiltration membrane has a higher retention rate for divalent cations, so it can be used for the separation of other multivalent cations and monovalent cations.
[0022] Traditional commercial nanofiltration membranes are negatively charged and have poor magnesium-lithium separation performance, and cannot effectively separate magnesium and lithium from salt lake brine. During the interfacial polymerization reaction, as the polyamide layer grows, the amine monomers that can diffuse into the reaction zone gradually decrease, while the acyl chloride in the organic phase always maintains a high concentration, resulting in the inevitable formation of a large number of carboxyl-terminated structures, which come from the hydrolysis of the residual acyl chloride groups. Therefore, nanofiltration membranes prepared by traditional interfacial polymerization are usually negatively charged. These membranes easily attract multivalent cations through electrostatic interactions, which is not conducive to the efficient separation of magnesium and lithium cations.
[0023] The present invention discloses a highly selective magnesium-lithium separation nanofiltration membrane based on a polyolefin-based membrane, and a preparation method and application thereof. By using a reverse interfacial polymerization method, using polyamine-based PEI as an aqueous phase monomer, using isophthaloyl chloride carrying two acyl chloride groups as an organic phase monomer, and preparing a nanofiltration (NF) membrane by reverse interfacial polymerization, the aqueous phase of the polyethyleneimine monomer containing rich amine groups is always located on the upper part of the phthaloyl chloride monomer with fewer acyl chloride groups, and the PA (polyamide) layer obtained after the polymerization reaction has a relatively large membrane pore size and a high positive charge density, and has a high magnesium-lithium separation performance in a solution with a high magnesium ion and lithium ion concentration ratio. The nanofiltration membrane prepared by the present invention has good magnesium-lithium separation performance, can be applied to water treatment and chemical separation fields, and the preparation method is simple to operate and can be applied to large-scale continuous production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1It is a schematic diagram of the preparation process of the present invention.
[0025] Figure 2 This is a scanning electron microscope image of Example 1 of the present invention.
[0026] Figure 3 This is a scanning electron microscope image of Example 2 of the present invention.
[0027] Figure 4 It is a magnesium-lithium separation performance diagram of comparative examples 1 and 2 of the present invention and examples 1 and 2 under different magnesium-lithium ratio solutions.
[0028] Figure 5 This is a stability performance test chart of Example 1 and Example 2 of the present invention for 24 consecutive hours. DETAILED DESCRIPTION
[0029] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0030] Materials used in the present invention: There is no particular limitation on the sources of all raw materials in the present invention and the following examples, and any raw materials may be commercially available.
[0031] Membrane flux detection method for highly selective lithium-magnesium separation membrane: The membrane permeation selectivity performance test system is used to test the membrane's water permeation flux and salt retention rate. The test system includes a pump, membrane pool, pipeline, regulating valve, pressure and flow detector, and the effective membrane area tested is 19.64cm 2 , the test pressure is 6 bar and the test temperature is 25±0.5℃.
[0032] The salt concentration for testing the single salt rejection rate: the concentration of MgCl2 and LiCl was 1000 ppm.
[0033] The mixed salt concentration and magnesium-lithium ratio for testing the separation performance of lithium and magnesium: The total concentration of MgCl2 and LiCl is 1000ppm, of which Mg 2+ / Li + =1:1, 5:1, 10:1, 20:1, 50:1, 100:1. Mg 2+ and Li + The concentration was measured using inductively coupled plasma optical emission spectroscopy (ICP-OES, VISTA-MPX, Varian).
[0034] The calculation formula of magnesium-lithium selectivity is as follows: Among them C Li,p and C Mg,p are Li in the permeate + and Mg 2+ Concentration (g / L), C Li,f and C Mg,f are Li in the permeate+ and Mg 2+ Concentration (g / L).
[0035] [Example 1]
[0036] A 0.5% polyethyleneimine (molecular weight 70000Da) solution was prepared as an aqueous phase mixed solution, and a 0.1% isophthaloyl chloride n-hexane solution was prepared as an organic phase mixed solution.
[0037] First, the organic phase mixture was placed on the surface of the polyolefin support membrane and adsorbed for 4 minutes, and the excess solution was removed. Then, the aqueous phase mixture was placed on the surface of the support membrane and reacted for 4 minutes. The excess solution was removed, and then the membrane was placed in a 60°C forced air drying oven for 15 minutes. The prepared lithium-magnesium separation membrane was placed in an isopropanol solution for activation for 15 minutes, and then the membrane was stored in deionized water for further testing of its separation performance.
[0038] Mg 2+ / Li + =1:1, 5:1, 10:1, 20:1, 50:1 and 100:1 mixed solution tests, the lithium-magnesium selectivity of the lithium-magnesium separation membrane was 16.82, 23.15, 23.41, 24.58, 25.28 and 27.26, respectively.
[0039] [Example 2]
[0040] A 0.5% polyethyleneimine (molecular weight 70000Da) solution was prepared as the aqueous phase mixed solution, and a 0.1% terephthaloyl chloride n-hexane solution was prepared as the organic phase mixed solution.
[0041] First, the organic phase mixture was placed on the surface of the polyolefin support membrane and adsorbed for 4 minutes to remove the excess solution. Then, the aqueous phase mixture was placed on the membrane surface to react for 4 minutes and the excess solution was removed. The membrane was then placed in a 60°C forced air drying oven for 15 minutes. The prepared lithium-magnesium separation membrane was placed in an isopropanol solution for activation for 15 minutes, and then the membrane was stored in deionized water for further testing of its separation performance.
[0042] Mg 2+ / Li + =1:1, 5:1, 10:1, 20:1, 50:1 and 100:1 mixed solution tests, the lithium-magnesium selectivity of the lithium-magnesium separation membrane was 14.78, 24.93, 28.01, 30.09, 31.46 and 45.64, respectively.
[0043] [Comparative Example 1]
[0044] The monomer in the organic phase mixed liquid of this comparative example is 0.1% phthaloyl chloride, and the rest is the same as in Example 1.
[0045] Mg 2+ / Li + =20:1, 50:1 and 100:1 mixed solution tests, the lithium-magnesium selectivity of the lithium-magnesium separation membrane was 12.76, 13.20 and 12.06 respectively.
[0046] [Comparative Example 2]
[0047] The monomer in the organic phase mixed liquid of this comparative example is 0.087% of trimesoyl chloride (TMC), and the rest is the same as in Example 2.
[0048] Mg 2+ / Li + =20:1, 50:1 and 100:1 mixed solution tests, the lithium-magnesium selectivity of the lithium-magnesium separation membrane was 13.22, 12.82 and 10.82 respectively.
[0049] Figure 1 The schematic diagram of the process of preparing the nanofiltration membrane of the present invention is shown in FIG. wherein the organic phase monomer is isophthaloyl chloride or terephthaloyl chloride, and the aqueous phase monomer is polyethyleneimine.
[0050] Figure 2 and Figure 3 The dense polyamide layer surface obtained in Examples 1 and 2; the highly selective lithium-magnesium separation membrane obtained in Examples 1 and 2 was characterized by scanning electron microscopy, and the obtained membrane surface morphology and cross-sectional morphology were analyzed. It can be seen that the surface of the highly selective lithium-magnesium separation membrane is smooth and dense and has no defects.
[0051] observe Figure 2 and Figure 3 The surface morphology on the left shows that the porous structure of the polyolefin base membrane is covered by the newly grown protrusions, indicating that a thin polyamide layer has been successfully formed. The surface of the highly selective lithium-magnesium separation membrane has many wrinkles and is relatively dense, and the surface morphology has not changed significantly. The reaction rate of the acyl chloride group and the amine group is relatively fast, forming a PA layer with a certain thickness. Figure 2 , Figure 3 As shown in the picture on the right: Figure 2 , Figure 3 The surface and cross-sectional morphology of the medium- and high-selectivity lithium-magnesium separation membranes showed that PEI and isophthaloyl chloride were successfully cross-linked on the top of the PE membrane to form a relatively dense PA separation layer.
[0052] Figure 4 The separation selectivity changes of the embodiment and the comparative example in mixed solutions with different magnesium-lithium ratios are compared. Figure 4As shown, the horizontal axis is the different magnesium-lithium ratios of the mixed solution, and the vertical axis is the magnesium-lithium separation coefficient of the nanofiltration membrane. It can be seen from the test results of the comparative examples and comparative examples that the comparative example uses traditional trimesoyl chloride or phthaloyl chloride as the organic phase monomer, and its lithium-magnesium selectivity decreases with the increase of the magnesium-lithium ratio. The magnesium-lithium separation coefficients of Example 1 and Example 2 increase with the increase of the magnesium-lithium ratio of the solution. The rising trend of the magnesium-lithium separation coefficient of Example 1 is relatively gentle, rising from 16.82 to 27.26. The magnesium-lithium separation coefficient of Example 2 rises faster, from 14.78 to 45.65. Therefore, terephthaloyl chloride is used in Example 2, which has a higher magnesium-lithium separation performance for high magnesium-lithium ratio solutions, and as the magnesium-lithium ratio continues to increase, the obtained nanofiltration membrane has better magnesium-lithium separation performance.
[0053] Figure 5 The lithium-magnesium separation membranes obtained in Examples 1 and 2 were subjected to a long-term stability test. After 24 hours of continuous performance testing, the NF membrane had a relatively stable retention rate for MgCl2. However, due to the long-term operation of the test instrument, the temperature inside the instrument rose, causing the permeability coefficient to fluctuate to a certain extent. The permeability coefficients of Examples 1 and 2 were basically stable at 3.5 and 3.2, respectively, indicating that the prepared lithium-magnesium separation membrane had good long-term stability.
[0054] The nanofiltration membrane prepared by the present invention has good magnesium-lithium separation performance in a high magnesium-lithium ratio mixed solution. At the same time, the preparation method is simple, the conditions are mild, the application range is wide, and it has good long-term operation stability. It can be applied to water treatment, seawater desalination, sewage treatment, dye purification, etc.
[0055] The above implementation modes are not limitations of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the scope of the technical solution of the present invention also belong to the protection scope of the present invention.
Claims
1. A method for preparing a highly selective magnesium-lithium separation nanofiltration membrane based on a polyolefin-based membrane, characterized in that: The preparation method is: First, a supporting base membrane is soaked in an organic phase solution containing an acyl chloride monomer to obtain a supporting base membrane impregnated with an organic phase monomer, and then the supporting base membrane is soaked in an aqueous phase solution containing an amine monomer for interfacial polymerization. Subsequently, the obtained nanofiltration membrane is activated to obtain a magnesium-lithium separation nanofiltration membrane.
2. The method for preparing a highly selective magnesium-lithium separation nanofiltration membrane based on a polyolefin-based membrane according to claim 1, characterized in that: The specific steps include: Step S1: dissolving isophthaloyl chloride or terephthaloyl chloride in an organic solvent to obtain an organic phase solution; Step S2: dissolving polyethyleneimine monomer in water to obtain an aqueous solution; Step S3: soaking the supporting base membrane with the organic phase solution prepared in step S1 to obtain a supporting base membrane infiltrated with organic phase monomers; Step S4: immersing the supporting base membrane soaked with the organic phase monomer obtained in step S3 in the aqueous phase solution prepared in step S2 to perform an interfacial polymerization reaction to obtain a polyamide thin film composite nanofiltration membrane; Step S5: heat-treating and alcohol-activating the polyamide thin film composite nanofiltration membrane obtained in step S3 to obtain a nanofiltration membrane with magnesium-lithium separation performance.
3. The method for preparing a highly selective magnesium-lithium separation nanofiltration membrane based on a polyolefin-based membrane according to claim 2, characterized in that: In the organic phase solution prepared in step S1, the concentration of isophthaloyl chloride or terephthaloyl chloride is 0.05-0.2 w / v%, and the organic solvent is n-hexane.
4. The method for preparing a highly selective magnesium-lithium separation nanofiltration membrane based on a polyolefin-based membrane according to claim 2, characterized in that: In the aqueous solution prepared in step 2, the molecular weight of the polyethyleneimine monomer is 700-70000 Daltons, and the concentration of the polyethyleneimine monomer is 0.1-2.0 wt%.
5. The method for preparing a highly selective magnesium-lithium separation nanofiltration membrane based on a polyolefin-based membrane according to claim 2, characterized in that: In the step S3, the supporting base membrane is a polyolefin porous membrane, and the soaking time is 1-10 minutes.
6. The method for preparing a highly selective magnesium-lithium separation nanofiltration membrane based on a polyolefin-based membrane according to claim 2, characterized in that: In the step S4, the reaction time of the interfacial polymerization reaction is 1-10 min.
7. The method for preparing a highly selective magnesium-lithium separation nanofiltration membrane based on a polyolefin-based membrane according to claim 2, characterized in that: In step S5, the heat treatment temperature is 30-95° C., the time is 15-60 min, the activation alcohol is isopropanol, and the activation time is 15-60 min.
8. A highly selective magnesium-lithium separation nanofiltration membrane obtained by the preparation method according to any one of claims 1 to 7.
9. Use of the highly selective magnesium-lithium separation nanofiltration membrane as claimed in claim 8 in cation separation.
Citation Information
Patent Citations
Method for preparing composite charged mosaic membrane via interfacial polymerization
CN101530748A
Method for preparing polyvinyl composite nanofiltration membrane through reversed-phase interfacial polymerization
CN113996182A
Thin-film composite nanofiltration membrane as well as preparation method and application thereof
CN114682103A
Composite nanofiltration membrane preparation method and composite nanofiltration membrane
CN115245756A
Method for preparing high-selectivity lithium-magnesium separation membrane
US20230182088A1
Cited By
Acid-resistant nanofiltration membrane as well as preparation method and application thereof
CN119733386A
Preparation method and application of cross-basement membrane back-diffusion in-situ growth ZIF modified polyvinyl polyamide positively charged nanofiltration membrane
CN120204962A
Preparation method and application of a kind of polyvinyl polyamide positively charged nanofiltration membrane modified by in-situ growth of ZIF across base membrane
CN120204962B
High-flux monovalent cation exchange membrane and application thereof in electrodialysis separation of lithium and magnesium
CN121695711A